2013
DOI: 10.1051/0004-6361/201220549
|View full text |Cite
|
Sign up to set email alerts
|

Hot subdwarf stars in close-up view

Abstract: Context. Hot subdwarf B stars (sdBs) are considered to be core helium-burning stars with very thin hydrogen envelopes situated on or near the extreme horizontal branch. The formation of sdBs is still unclear as well as the chemical composition of their atmospheres. The observed helium depletion is attributed to atmospheric diffusion. Metal abundances have been determined for about a dozen sdBs only resulting in puzzling patterns with enrichment of heavy metals and depletion of lighter ones. Aims. We present a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
43
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 74 publications
(91 reference statements)
9
43
0
Order By: Relevance
“…Their models, which assume extra mixing but no stellar-wind mass loss, are in general agreement with the observed metal abundances of sdB stars (Geier 2013) as well as the helium abundances for T eff > 25 000 K. Furthermore, they show that diffusion effects reach far deeper than the stellar atmospheres themselves and should also be dominant in the He + /He 2+ convection zone (Moehler, Michaud, priv. comm.…”
Section: Helium Sequencessupporting
confidence: 66%
“…Their models, which assume extra mixing but no stellar-wind mass loss, are in general agreement with the observed metal abundances of sdB stars (Geier 2013) as well as the helium abundances for T eff > 25 000 K. Furthermore, they show that diffusion effects reach far deeper than the stellar atmospheres themselves and should also be dominant in the He + /He 2+ convection zone (Moehler, Michaud, priv. comm.…”
Section: Helium Sequencessupporting
confidence: 66%
“…After making these symmetric we found that KIC 7664467 has an NLTE temperature of T eff = 27 440 ± 120 K, surface gravity of log g = 5.382 ± 0.019 dex, and He abundance of log(nHe/nH) = −2.57 ± 0.05 dex, which places it among most of the slow pulsating sdB stars. The metallicity of KIC 7664467 fits in the general abundance profile of sdB stars (Geier 2013): helium and light metals are depleted, while Fe is near or somewhat above the solar abundance. The nuclear history of sdB stars is not reflected by their surface parameters, because diffusion processes change their surface abundances (Michaud et al 2011).…”
Section: Model Atmosphere Analysismentioning
confidence: 86%
“…The C ii lines at 4267 Å, as well as the Si iii lines at 4552, 4567, 4574, and 5739 Å, are strong enough to measure both the abundances and the rotational broadening in the way described in Geier (2013). The v rot sin i = 48 ± 2 km s −1 measured from those lines is somewhat smaller than the one measured from the Balmer and helium lines.…”
Section: Atmospheric Parameters and Rotational Broadeningmentioning
confidence: 90%
“…In the course of our studies of sdB stars at high spectral resolution (Geier et al 2010(Geier et al , 2011aGeier 2013), the sdB star SB 290 caught our attention because of its unusual line shapes. SB 290 (CD−38 222) was discovered as a Btype star in the objective prism survey of the south Galactic pole region by Slettebak & Brundage (1971).…”
Section: Introductionmentioning
confidence: 99%